The Implementation of Doing Self-Assessment in Higher Education - Nadella Lesmana; Umi Rokhyati (English Department - University of Sultan Ageng Tirtayasa, 2020)
This study aims to discover how undergraduate students conducted self-assessments of their learning process and outcomes, and how much doing self-assessment could contribute to the learning achievement. This research applied a qualitative method. The authors utilized interviews to collect data and wrote them down as the results of the analysis. Based on the results of the interviews, six students responded to the survey regarding conducting self-assessment in the learning process revealing that the benefit of doing self-assessment for students was that they could introspect themselves in the learning process, the self- assessment had significantly contributed to time management during the learning process. In addition, self-assessment could motivate students to improve their ability to learn from previous results. Students could also evaluate what had been done in the learning process. Evaluation results were also significant for students in conducting self-assessments. Hence, students understood the extent of their ability to learn, which was better or worse than before, in every problem during the study process.